Analisis Pengaruh Penerapan Akuntansi Syariah Terhadap Keputusan Pembelian Konsumen di Shopee - Putri, Annisa Liana; Salsabilla, Annisa; Jannah, Miftahul; Ramadhani, Alindri Tita; Azwari, Peny Cahaya (JAB (Jurnal Akuntansi & Bisnis), 2025)
This study aims to analyze the impact of the implementation of Islamic accounting on consumer purchasing decisions on the Shopee e-commerce platform. The method used in this study is a literature review, selecting relevant and comparable articles on Islamic accounting, e-commerce transactions, and consumer behavior among Muslims. These articles were analyzed to identify the relationship between the implementation of Islamic accounting principles and purchasing decisions on Shopee. The findings indicate that the application of Islamic accounting principles, such as transparency, fairness, and adherence to Sharia, significantly influences purchasing decisions, with consumers who have high religiosity being more likely to choose transactions that comply with Islamic principles. However, other factors such as price and transaction convenience also affect purchasing decisions. This study provides insights into the importance of implementing Islamic accounting in e-commerce to create ethical transactions that align with Islamic principles.